“If it’s gonnae make things better then I don’t have any issue”: Perspectives of People Who Use Drugs on the Use of Administrative Data for Research - Marryat, Louise; Booth, Hazel; Gray, Sarah; Mohan, Andrea; Robertson, Senga; Thekkumkara, Sreekanth; Biazus-Dalcin, Camila (International Journal of Population Data Science, 2026)
Introduction Routinely-collected data are increasingly used to study outcomes among marginalised communities, including people who use drugs, because they capture groups often under-represented in traditional research. However, little is known about how this population feels about researchers using their data, particularly given the stigma they frequently encounter. Objectives This public involvement and engagement study explored the views of people who use(d) drugs on the use of their routinely-collected data in research, with the aim of informing future work in this field. Methods Participants were recruited through a recovery organisation in Southeast Scotland, UK. Two deliberative focus groups were conducted (n=11 and n=12). Each session began with a short introduction to routinely-collected data and its research uses, followed by discussion guided by a topic schedule and a creative participatory activity. Thematic analysis was carried out using NVivo v15. Results Five overarching themes were identified. Participants expressed very low awareness that their data were being used in research and highlighted the need for clearer and more accessible transparency about data processes. Concerns about consent and personal control were common, with many wanting greater involvement or choice in how their information is used. Participants strongly supported data use when it served a clear and meaningful public benefit and when researchers were held accountable for how findings were used. Discussions also reflected worries about the accuracy, completeness, and fairness of the data held about them, particularly where misunderstandings or assumptions might be recorded. Underpinning all themes was a pervasive sense of fear and mistrust toward services that collect data, which participants felt could limit honest disclosure and ultimately affect data quality. Conclusions People who use drugs were broadly supportive of their routinely-collected data being used in research with clear social value and transparency. However, pervasive mistrust of data-collecting services may affect data quality and should be carefully considered by researchers.